Foreign Law Bonds: Can They Reduce Sovereign Borrowing Costs? - Julian Schumacher; Marcos Chamon; Christoph Trebesch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The Greek debt restructuring of 2012 showed that the legal terms of sovereign bonds can protect creditors against losses, in particular the type of governing law. This paper studies whether sovereign bonds that are issued in foreign jurisdictions trade at a premium vis-a-vis domestic-law bonds. We use the Eurozone between 2007 and 2014 as a unique testing ground to assess this ``legal safety premium'' and collect secondary market bond yield data for the near-universe of Eurozone government bonds issued in foreign jurisdictions. Controlling for currency risk, liquidity risk, and term structure, we find that foreign-law bonds indeed carry lower yields on average. But a sizable premium only emerges for large values of credit risk (CDS spreads beyond 500bp). At those levels, a 100bp increase in CDS spreads is associated with a 30-80bp larger yield premium on foreign-law bonds. In contrast, we do not find a premium for countries that are perceived as low risk. These results indicate that sovereigns in distress can, at the margin, borrow at lower rates under foreign law.
Keywords: G12; G15; F34; 330